Generating innovations through analogies: An empirical investigation of knowledge brokers - Katharina Kalogerakis; Cornelius Herstatt; Christian Lüthje (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2005)
In this paper we explore how knowledge brokers - specialised design and engineering companies offering services to clients in diverse industries - use analogies for product development. Our research is based on interviews with project leaders of 13 knowledge brokering companies. The interviews focused on product development projects in which analogies were used. First, we categorize these cases according to the motivation to use analogies (efficiency vs. innovativeness). Second, we describe and analyse the process of using analogies. Our results show that analogies are frequently and very pragmatically applied throughout the whole development process. We also found that individual characteristics of the persons participating in such projects are the crucial factor that influences the outcome of the project.
urn:nbn:de:gbv:830-opus-1016
Keywords: 650; product development; knowledge brokers; analogy